Digital Financial Inclusion as A Catalyst for Blue Economy Development: The Role of Regional Development Banks in Strengthening Fisheries and Marine Sector Revenue in East Java - Hermita Hermita; Nurliah Nurdin; Muhammad Taufiq; R Luki Karunia (Balai Besar Riset Sosial Eonomi Kelautan dan Perikanan, 2025)
Indonesia's blue economy holds significant potential for regional economic development, yet coastal and fisheries communities remain underserved by formal financial services. This study examines how digital transformation in Regional Development Banks (BPDs) can drive financial inclusion and enhance revenue generation in the marine and fisheries sector. Using Bank Jatim as a case study, this research employs a qualitative approach with in-depth interviews and document analysis involving stakeholders from banking, regional government, fisheries agencies, and coastal community representatives. Findings reveal that digital financial services—including mobile banking, digital payment systems for fisheries transactions, and regional tax digitization—significantly improve access to capital for small-scale fishers and aquaculture businesses while accelerating Regional Own-Source Revenue (PAD) collection from marine resource levies. The study proposes an integrated Blue Economy Digital Finance Model encompassing four dimensions: (1) digital infrastructure for coastal financial inclusion, (2) adaptive institutional governance linking banks, fisheries agencies, and coastal communities, (3) capacity building for digital literacy among fishing households, and (4) collaborative policy frameworks aligning blue economy goals with regional fiscal sustainability. This research contributes to the literature on blue economy financing and provides policy recommendations for leveraging digital banking to strengthen Indonesia's marine and fisheries sector development.